Experimental realization of an all-(RE)BaCuO hybrid trapped field magnet lens generating a 9.8 T concentrated magnetic field from a 7 T external field. (19th March 2021) - Takahashi, Keita; Fujishiro, Hiroyuki; Namba, Sora; Ainslie, Mark D
Abstract: In this work, we have verified experimentally an all-(RE)BaCuO hybrid trapped field magnet lens (HTFML) using only one cryocooler and a special technique named the 'loose contact method'. In the experimental setup, only the inner magnetic lens was tightly connected to the cold stage and cooled at all times, and the outer trapped field magnet (TFM) cylinder was loosely connected to the cold stage before the magnetizing process by introducing a gap between the outer TFM and cold stage of the cryocooler. As a result, the superconducting state for zero-field cooled magnetization of the inner magnetic lens and the non-superconducting (normal) state for field-cooled magnetization of the outer TFM cylinder can co-exist at the same time. A maximum concentrated field of B c = 9.8 T was achieved for the magnetizing process with an applied field of B app = 7 T in the present HTFML, consistent with the numerical estimation in our previous conceptual study. These results validate the HTFML concept as a compact and desktop-type magnet device that can provide 10 T-class magnetic field enhancement from the viewpoint of the magnetizing method. However, during magnetization with a higher B app of 10 T, thermal instability of the outer stacked TFM cylinder caused flux jumps to occur, resulting in mechanical fracture of multiple bulks. These results suggest that the further development of a practical cooling method that can realize a stable and controllable cooling process for each part of the HTFML is necessary based on fundamental studies relating to the thermal stability of the large stacked TFM cylinder.